International postmodernism. Theory and literary practice. Edited by Hans Bertens and Douwe Fokkema. John Benjamins Publishing company, Amsterdam/ Philadelphia, 1997, σελ. 581. - Σιαφλέκης Ζ. (Σύγκριση/Comparaison/Comparison, 2017)
No abstract available